Sensitivity of recently naturalised Digitaria spp. populations to 4‐hydroxyphenyl pyruvate dioxygenase‐ and acetolactate synthase‐inhibiting herbicides in maize. (27th January 2017) - De Cauwer, B; Dendauw, E; Claerhout, S; Biesemans, N; Reheul, D
Summary: Until recently, Digitaria aequiglumis var. aequiglumis, native to South America, and Digitaria ciliaris subsp. nubica, native to Northeast Africa, were completely overlooked in Belgium due to their close morphological resemblance to Digitaria sanguinalis and Digitaria ischaemum . One of the possible reasons for their expansion in maize fields, besides for example the lack of crop rotation, might be a lower sensitivity to post‐emergence herbicides acting against panicoid grasses. Dose– response pot experiments were conducted in the glasshouse to evaluate the effectiveness of four foliar‐applied HPPD‐inhibiting herbicides (mesotrione, sulcotrione, tembotrione, topramezone) and two foliar‐applied ALS‐inhibiting herbicides (foramsulfuron, nicosulfuron) for controlling Belgian populations of D. aequiglumis and D. ciliaris subsp. Nubica, as well as local D. sanguinalis and D. ischaemum populations .  In another dose–response pot experiment, the influence of growth stage at time of herbicide application on efficacy of topramezone and nicosulfuron for Digitaria spp. control was evaluated. In general, D. aequiglumis and D. ciliaris subsp. nubica populations were less sensitive to HPPD inhibitors than D. ischaemum and D. sanguinalis populations, except for D. aequiglumis treated with topramezone. Contrary to other herbicides tested, topramezone adequately controlled all D. aequiglumis populations at doses well below maximum authorised field dose. All species tested showed a progressive decrease in sensitivity to topramezone and nicosulfuron with seedling age. A satisfactory post‐emergence control of Digitaria species in the field will require appropriate choice of herbicide and dose, as well as more timely application.